Severe hemorrhage complicating early transplant nephrectomy due to sepsis - Jacob A Akoh; Tahawar Rana (Saudi Journal of Kidney Diseases and Transplantation, 2016)
Compared to the general population, transplant patients receiving immuno- suppression have an increased risk of wound and systemic infection that might lead to hemorrhage. We present a case of severe bleeding from the external iliac artery secondary to a pelvic abscess following renal transplantation and transplant nephrectomy. A 73-year-old man received an extended criteria donor organ from a 49-year-old person who died from systemic sepsis. The patient bled from the Carrel′s patch while awaiting a computed tomographic scan- guided drainage of an infected peritransplant collection. At exploration, a nonviable allograft surrounded by about 1 L of thick pus was removed. Bleeding from a 2 mm hole in the Carrel′s patch was repaired by prolene suture as the external iliac vessels could not be mobilized due to a frozen pelvis. The patient died 72 h later from a massive bleed confirmed at postmortem to have originated from the external iliac artery distal to the anastomosis. Diversion of blood flow away from an affected area (with or without excision of the infected vessels) through a bypass procedure probably represents the best option in avoiding such sequelae.